Impact of Ramadan Tafsir on the Contemporary Muslims in Iwoland - Badmus, Saheed Adewale (ADDIN, 2024)
Tafsīr is one of the religious activities in the month of Ramaḍān that do not only sustain the spirituality of the Muslims but also strengthen the socio-moral aspects of their lives. But that do the significance of Ramadan Tafsīr in the Islamic societies cannot be underrated as it has positively impacted the Muslim Ummah in general and Iwo town in particular. It is therefore necessary to expose and document its impacts on the Muslim Ummah in Iwo land with a focus on Iwo town. To achieve this, historical, analytical and phenomenological methods of research had been used. In accounting for the historical background of Iwo and Ramadan Tafsīr in the town, historical method had been employed while analytical method was used in explaining the impact of Ramaḍān Tafsīr on the Muslim Ummah in Iwo town. Phenomenological method was used in relating these impacts to the people of Iwo town so as to determine the extent to which these impacts have taken effects on their lives. The paper discovered that the Impacts cut across the socio-moral and economic as well as spiritual aspects of the Muslims in Iwo town. It also revealed that most of the Mosques where Ramaḍān Tafsīr is done in Iwo town are facing challenges among which are non recording of Tafsīr; not broadcasting it on social media and lacking public address system as the Muffassirun are always talking on top of their voices. The paper concluded by advocating good treatment of the Mufassirūn by the well to do Muslims in the town as well as prompt recording and live broadcasting of the Tafsīr with the intention of wider coverage.